2008
DOI: 10.1001/archdermatol.2007.5
|View full text |Cite
|
Sign up to set email alerts
|

Annual Direct and Indirect Health Care Costs of Chronic Idiopathic Urticaria

Abstract: To estimate annual direct and indirect health care costs in patients with chronic idiopathic urticaria (CIU) managed with conventional therapies.Design: A cost analysis consisting of a survey-guided and retrospective medical record review of direct and indirect health care costs from a societal perspective in patients with CIU.Setting: The Johns Hopkins University allergy and dermatology ambulatory clinics.Participants: Fifty adults with active CIU were recruited in sequential order. Individuals who were takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
95
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 8 publications
4
95
1
6
Order By: Relevance
“…CU primarily affects the working population as the peak age of CU onset is between 20 and 40 years 4. Patients with CU experience an underestimated emotional and psychological burden which influences sleep and daily activities and restricts work ability and social life 4, 5, 6, 7, 8, 9. HRQoL impairment in CU increases with disease severity,6, 10 prevalence of comorbid psychological conditions11, 12, 13 and several autoimmune conditions 14, 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CU primarily affects the working population as the peak age of CU onset is between 20 and 40 years 4. Patients with CU experience an underestimated emotional and psychological burden which influences sleep and daily activities and restricts work ability and social life 4, 5, 6, 7, 8, 9. HRQoL impairment in CU increases with disease severity,6, 10 prevalence of comorbid psychological conditions11, 12, 13 and several autoimmune conditions 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, the burden of CU translates into costs to healthcare payers and the society. Medication, outpatient costs and loss of productivity due to the absence from work are major cost drivers and increase with disease severity 8, 18. Work and activity impairment in CU patients is twice as high as reported in non‐CU patients 6, 10.…”
Section: Introductionmentioning
confidence: 99%
“…En 2014 se publicó una historia clínica de UC que proporcionó una herramienta para ayudar al diagnós-tico y evaluación del estado de la enfermedad en la práctica diaria. 50 Sin embargo, en esa propuesta no se pregunta sobre características específicas importantes en el diagnóstico clínico de los subtipos de UC como color, características que acompañan a la lesión, distribución de las erupciones, síntomas asociados y otros posibles agentes etiológicos; ni se proporciona referencia bibliográfica de apoyo para cada pregunta, como sí hicimos con la nuestra. 3,50,51 En los últimos 30 años, la atención se ha centrado en nuevas formas de entender y manejar la UC, desde la reciente adición de nuevos fármacos al arsenal terapéutico, la actualización de las guías de práctica clínica y la publicación de conceptos fisiopatológicos.…”
Section: Discussionunclassified
“…50 El médico debe considerar la posibilidad de neoplasias malignas neuroendocrinas, recomienda realizar pruebas de rutina de detección de anticuerpos antitiroideos y complemento y considerar la detección de niveles elevados de anticuerpos antiparietales.…”
unclassified
“…CU has been defined as a daily or almost daily occurrence of wheals and/or angioedema, occurring over a period of ≥6 weeks (17)(18)(19). Furthermore, the direct cost of CU, in terms of healthcare visits, investigation and treatment, is high (20). Several aetiological factors have been associated with the onset of CU and it was suggested that the condition has an autoimmune basis (21,22).…”
Section: Discussionmentioning
confidence: 99%